# If four points A(a¯),B(b¯),C(c¯)andD(d¯) are coplanar, then show that [a¯b¯c¯]+[b¯c¯d¯]+[c¯a¯d¯]=[a¯b¯c¯]. - Mathematics and Statistics

Sum

If four points "A"(bar"a"), "B"(bar"b"), "C"(bar"c") and "D"(bar"d") are coplanar, then show that [(bar"a", bar"b", bar"c")] + [(bar"b", bar"c", bar"d")] + [(bar"c", bar"a", bar"d")] = [(bar"a", bar"b", bar"c")].

#### Solution

If points "A"(bar"a"), "B"(bar"b"), "C"(bar"c") and "D"(bar"d") are coplanar, then bar"AB", bar"AC", bar"AD" are also coplanar.

∴ bar"AB"*(bar"AC" xx bar"AD") = 0        .......(i)

Here, bar"AB" = bar"b" - bar"a"

bar"AC" = bar"c" - bar"a"

bar"AD" = bar"d" - bar"a"

From (i), we get

(bar"b" - bar"a").[(bar"c" - bar"a") xx (bar"d" - bar"a")] = 0

∴ (bar"b" - bar"a").[bar"c" xx bar"d" - bar"c" xx bar"a" - bar"a" xx bar"d" + bar"a" xx bar"a"] = 0

∴ (bar"b" - bar"a")*[bar"c" xx bar"d" - bar"c" xx bar"a" - bar"a" xx bar"d" + bar"a" xx bar0] = 0

∴ (bar"b" - bar"a")*[bar"c" xx bar"d" - bar"c" xx bar"a" - bar"a" xx bar"d"] = 0

∴ bar"b"*(bar"c" xx bar"d") - bar"b"*(bar"c" xx bar"a") - bar"b"*(bar"a" xx bar"d") - bar"a"*(bar"c" xx bar"d") + bar"a"*(bar"c" xx bar"a") + bar"a"*(bar"a" xx bar"d") = 0

∴ [(bar"b", bar"c", bar"d")] - [(bar"b", bar"c", bar"a")] - [(bar"b", bar"a", bar"d")] - [(bar"a", bar"c", bar"d")] + [(bar"a", bar"c", bar"a")] - [(bar"a", bar"a", bar"d")] = 0

∴ [(bar"b", bar"c", bar"d")] - [(bar"a", bar"b", bar"c")] + [(bar"a", bar"b", bar"d")] + [(bar"c", bar"a", bar"d")] + 0 + 0 = 0

∴ [(bar"a", bar"b", bar"d")] + [(bar"b", bar"c",bar"d")] + [(bar"c", bar"a", bar"d")] = [(bar"a", bar"b", bar"c")]

Concept: Representation of Vector
Is there an error in this question or solution?